Competencias del animador turístico: aproximaciones del punto de vista galo - Ángel Hernández Morales (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2014)
The main objective of this article is to present the fundamentals regarding Competencies Animator, with the intention of providing a source of information to feed and create a study guide for those interested in this area of tourism. Added to this, it is my duty to explain that this document was conceived thanks to the meeting I made in various seminars in the country of France during the Update Program for Executives AMESTUR-VTF-UNAT 2014, which aimed to discover the social tourism, its origin, development and its benefits to the local economy, the importance of sociocultural and professional training of animators. These seminars were chaired by French experts in the field, who have adopted the Social Tourism as a life and show the importance of the Tourism Skills Camp for developing it. The competencies mentioned are Leadership, Empathy, Proactivity, Creativity, Organization and Training.